2019
DOI: 10.1016/j.nlm.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of autonomic and central events during sleep benefits declarative memory consolidation

Abstract: While anatomical pathways between forebrain cognitive and brainstem autonomic nervous centers are well-defined, autonomic–central interactions during sleep and their contribution to waking performance are not understood. Here, we analyzed simultaneous central activity via electroencephalography (EEG) and autonomic heart beat-to-beat intervals (RR intervals) from electrocardiography (ECG) during wake and daytime sleep. We identified bursts of ECG activity that lasted 4-5 seconds and predominated in non-rapid-ey… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 53 publications
(72 reference statements)
10
39
1
Order By: Relevance
“…It's been hypothesized that in the case of the K-complex, the recruited synchronized EEG response acts as a mechanism to decrease cortical arousal, suggesting that the heart-rate acceleration (tachycardia, or HR bursts) can be viewed as peripheral response of arousal from sleep. Taken together, the subsequent heart-rate deceleration that de Zambotti et al (2016) showed and the surge of HF that Naji et al (2019) and the current study found may reflect a feedback effect of arousal showing an inertial effect once the arousal stimulus is removed. Alternatively, arousal and post-arousal periods may modulate the autonomic system reflecting the activation-deactivation of neuronal oscillations intrinsically regulated by the cyclic arousability of the sleepy brain (Schnall et al, 1999;Sforza et al, 1999;Ferri et al, 2000).…”
Section: Heart-brain Interaction During Sleep: Findings and Potentialsupporting
confidence: 60%
See 1 more Smart Citation
“…It's been hypothesized that in the case of the K-complex, the recruited synchronized EEG response acts as a mechanism to decrease cortical arousal, suggesting that the heart-rate acceleration (tachycardia, or HR bursts) can be viewed as peripheral response of arousal from sleep. Taken together, the subsequent heart-rate deceleration that de Zambotti et al (2016) showed and the surge of HF that Naji et al (2019) and the current study found may reflect a feedback effect of arousal showing an inertial effect once the arousal stimulus is removed. Alternatively, arousal and post-arousal periods may modulate the autonomic system reflecting the activation-deactivation of neuronal oscillations intrinsically regulated by the cyclic arousability of the sleepy brain (Schnall et al, 1999;Sforza et al, 1999;Ferri et al, 2000).…”
Section: Heart-brain Interaction During Sleep: Findings and Potentialsupporting
confidence: 60%
“…Though the functional significance of CNS-ANS couplings during sleep is only beginning to be explored, we hypothesize that ACE activity may play an important role in hippocampalprefrontal cognitive enhancement. Results from our group have shown ACE (SWA and spindles) contributions to long-term, episodic memory(Naji et al 2019), as well as WM gains (SWA, current study). In addition, recent studies implicate frontal SWA with improvement in WM, a cognitive ability strongly supported by the prefrontal cortex(Wager and Smith 2003).…”
supporting
confidence: 56%
“…Nonetheless, BOLD signal results from a complex interplay between neuronal and vascular events (Friston et al, 2000, Obrig et al, 2000, Logothetis et al, 2001, Shmueli et al, 2007, Bianciardi et al, 2009, Webb et al, 2013, Yuan et al, 2013, Rayshubskiy et al, 2014, Chang et al, 2016, Tong et al, 2016, where oscillations in the signal could be affected by vasomotion (~0.1 Hz intrinsic fluctuations in arteriole diameter) or by autonomous nervous system activity (cardiac or respiratory activity). Notably, dynamic coupling between cardiac activity and spindle or slow wave activity has been reported during human sleep (Lechinger et al, 2015, Lin et al, 2016, Menson et al, 2016, de Zambotti et al, 2018, which predicts the post-sleep improvements in cognitive performances (Naji et al, 2018), consistent with the visceral influences on brain and behavior observed during wake (Critchley andHarrison, 2013, Park et al, 2014). Moreover, vasomotion is entrained by neuronal oscillations of similar frequency (Mateo et al, 2017).…”
Section: Potential Mechanisms Underlying Bold Oscillations In Sleepmentioning
confidence: 74%
“…Although sleep studies generally implement heart rate measurements, few have analyzed its association with memory. Using daytime nap protocols, Whitehurst, Cellini, Mcdevitt, Duggan, and Mednick () found HF during rapid eye movement (REM) to be positively associated with performance improvement on a declarative remote associates test, whereas Naji, Krishnan, Mcdevitt, Bazhenov, and Mednick () found HF during N2 to be positively correlated with improvement on a declarative face–name association task. Investigations for full‐night sleep protocols as well as the procedural memory domain are as of yet lacking, yet longer sleep duration may provide a clearer insight into HRV during sleep and its relation to OMC.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicate that daytime naps prevent the memory deterioration observed during an identical period of daytime wakefulness, whereas full‐night sleep may result in significant improvements in performance (van Schalkwijk et al., ). Following the recent studies on HRV and OMC during a daytime nap (Naji et al., ; Whitehurst et al., ), the present study re‐analyzed the procedural dataset of the full‐night study to investigate long‐term (7 days) memory performance changes and associations between SpA and HRV as potential mediators of OMC that are underrepresented in the current literature. Participants were trained on a procedural mirror‐tracing task for which short‐ (12 hr) and long‐term (7 days) performance changes were evaluated.…”
Section: Introductionmentioning
confidence: 99%